Ultrasound-Guided Continuous Rhomboid Intercostal and Sub-Serratus Plane Block Comparison of Thoracoscopic Intercostal Nerve Block After Thoracoscopic Surgery: A Prospective Randomized Controlled Study - Wang S; Wang H; Chen X; Li M; Xu D (Journal of Pain Research)
Songdi Wang, Hong Wang, Xuemei Chen, Min Li, Danyang Xu Department of Anesthesiology, Affiliated Hospital of Chifeng University, Chifeng, 024000, People’s Republic of ChinaCorrespondence: Xuemei Chen, Email Chenxuemei.1968@163.comPurpose: Thoracic surgery is among the most painful surgeries, postoperative pain can lead to a poor prognosis. This study aimed to explore the analgesic effect of ultrasound-guided continuous rhomboid intercostal and sub-serratus (RISS) plane block Comparison of thoracoscopic intercostal nerve block (ICNB) on postoperative pain management and recovery in patients who underwent Video-Assisted Thoracic Surgery (VATS) Lobectomy.Methods: This prospective randomized controlled study enrolled patients after VATS Lobectomy who received ultrasound-guided continuous RISS plane block (RISS group) or ICNB (Control group) for postoperative pain. The primary outcome was the visual analogue scale (VAS) score. The secondary outcomes included non-invasive blood pressure (NIBP), heart rate (HR), the time to ambulation after surgery, the timing of drain removal, and the duration of postoperative hospitalization.Results: A total of 98 participants were collected (53.08 ± 13.63; 43 (43.88%) males); each group included 49 patients. The RISS group displayed significantly lower visual analogue scale (VAS) scores during rest and when coughing at postoperative 12, 24, and 48h compared to the Control group (P < 0.001). The total consumption of sufentanil and remifentanil was smaller in the RISS group than in the control group. The NIBP,HR in the RISS group were significantly lower than in the Control group at immediately after skin incision (T1), upon entering the thoracic cavity (T2), 5 min after entering the thoracic cavity (T3) (P < 0.001). The patients in the RISS group were more likely to exhibit a shorter time to the first postoperative ambulation compared to the Control group (8.84 ± 2.87,15.43 ± 4.50, P < 0.001).Conclusion: Continuous RISS may be a safe and effective strategy for postoperative pain management after thoracoscopic surgery.Keywords: postoperative pain, thoracoscopic surgery, rhomboid intercostal and sub-serratus plane block, intercostal nerve block